A Perspective on Computing Research Management - Levin, Roy (Operating Systems Review, 2007)
This paper offers a perspective on a particular set of principles that have guided the development and enabled the success of several noteworthy corporate research labs in computer science. The paper examines the differences between the corporate computing research environment and academia, then describes the model for managing research that Microsoft Research employs, illustrating how it reflects those differences and what the consequences are.